Microstructure evolution of MeB2 (Me=Zr, Ti) powders prepared by borothermal reduction during heat treatment at 1000°C–1800°C. Issue 17 (1st December 2019) - Zeng, Ling-Yong; Liu, Qiu-Yu; Sun, Shi-Kuan; You, Yang; Guo, Wei-Ming; Wu, Li-Xiang; Lin, Hua-Tay
Abstract: Microstructure evolution of MeB2 (Me = Zr, Ti) powders prepared by borothermal reduction of the corresponding oxides with boron under vacuum was investigated after heat-treatment at different temperature. The existence of the by-product B2 O3 resulted in the coarsening of faceted ZrB2 particles at 1550 °C or below, whereas B2 O3 showed almost no effect on the size and morphology of TiB2 or Zr0·98 Ti0·02 B2 particles. It could be concluded that the coarsening of ZrB2 in the temperature range of 1000 °C–1550 °C was caused by the dissolution-reprecipitation mechanism. While, few effects on TiB2 or Zr0·98 Ti0·02 B2 was found in this temperature range. When subject to higher temperature in B2 O3 -free environment, the growth was inversely evidenced on TiB2 and Zr0·98 Ti0·02 B2 but the growth of ZrB2 particle could be retained, indicative of the surface diffusion, which controlled the particle growth at high temperature.